Alternative Solutions to the Problems of Islamic Education (Ontological Problems of Islamic Education) - Madhar Amin (STIT Attaqwa, 2024)
Education is part of an investment in the future, a societal investment as well as a national investment aimed at advancing and enlightening the nation's life. Therefore, to achieve these goals, education is continually directed towards addressing several issues related to national and communal matters. Problem Formulation: What are the ontological problems in Islamic education and what are the alternative solutions to these ontological problems in Islamic education. Problem Objectives: To understand the ontological problems in Islamic education and explore alternative solutions to these issues. The research method employed is literature review. Results and Discussion: This paper discusses the ontological issues in Islamic education. Ontology is a branch of philosophy that deals with the essence of life. The problems in Islamic education that concern ontology necessitate the establishment of foundations, life principles, and a pattern of human thinking in the administration of Islamic education.